Physiological ecology of alpine plants - Spomer, George Guy, author; Salisbury, Frank B., advisor; Ward, Richard T., committee member; Cole, C. Vernon, committee member; Ross, Cleon W., committee member (Colorado State University. Libraries, 1962)
A physiological ecology study was made in the alpine areas of Mt. Evans and Rocky Mountain National Park, Colorado and in controlled environments. Alpine environmental factors were measured and analyzed. Growth chambers and other controlled environment facilities that were used to study plant processes are described. Alpine plant temperatures were measured in the field along with certain environmental factors and the data were analyzed for correlations. Plant temperatures of up to 32 C were recorded, and differences between the plant and air temperatures were frequently more than 20 C. The plant temperatures correlated most strongly with air temperatures, while the plant-air temperature gradient had the highest correlation with maximum light intensity, although the factors considered did not have a large effect on the plant-air temperature gradient. In both cases the form of the plant influenced plant temperatures and the gradient to a considerable degree. The growth and vegetative development of alpine plants were affected to a considerable extent by the average daily temperature. Temperatures of 18 to 27 C increased the initial growth rate and development but were found to be detrimental to the plants after a prolonged length of exposure. Temperatures of around 12 to 14 C seemed to be optimal for the overall growth of alpine plants. Treatments with GA, shading, or wind shielding did not alter the cushion plant form in the field except that GA caused the internodes of Trifolium nanum to elongate. These mat plants usually lost their cushion form at lower elevations. The flowering of Geum turbinatum was investigated extensively since this species normally does not flower at lower elevations unless it has initiated flower primordia in the field and has also received a period of cold temperatures. CCC, however, promoted the initiation of flower primordia and flower development in many individuals under greenhouse conditions. Cold treatment and UV radiation may also result in the initiation of flower primordia. Dormancy of several species of alpine plants was studied in the field but no correlations were found between environmental factors and the dormancy response. Dormancy in some species was induced by average daily temperatures of less than 8 C depending upon the nutritional state of the plants. No plants were induced to go into dormancy by photoperiods alone, nor was there any effect from the treatments of red and far-red light. GA retarded the dormancy of mat plants in the field when applied 60 days in advance of the time of dormancy. GA also increased the rate of breaking dormancy in some mat plant species under greenhouse conditions while NAA retarded growth and the breaking of dormancy in these same cushion plants.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Mountain plants; Plant ecology